2021
DOI: 10.3390/pr9071221
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Syntheses and Sources of Nanomaterials for Microbial Fuel/Electrolysis Cell Applications: An Overview of Recent Progress

Abstract: The use of microbial fuel cells (MFCs) is quickly spreading in the fields of bioenergy generation and wastewater treatment, as well as in the biosynthesis of valuable compounds for microbial electrolysis cells (MECs). MFCs and MECs have not been able to penetrate the market as economic feasibility is lost when their performances are boosted by nanomaterials. The nanoparticles used to realize or decorate the components (electrodes or the membrane) have expensive processing, purification, and raw resource costs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…Considering that the membranes and electrodes account for over 80% of the total MFC costs, a considerable reduction up to 30-40% can make these technologies more competitive to other (waste)water treatment methods. Utilization of inexpensive raw materials (including recycled or naturally occurring materials) as well as the development of facile and cost-effective methods can be considered a potential approach to reduce the costs of MFC fabrication [189]. For instance, Feng et al [190] concluded that among the high-performance materials, SS electrodes (SUS 304) are the cheapest option (21 k$/m 3 ), followed by titanium plate and graphite felt (30 k$/m 3 , and 25-75 k$/m 3 , respectively).…”
Section: Sustainability Aspects and Future Outlookmentioning
confidence: 99%
“…Considering that the membranes and electrodes account for over 80% of the total MFC costs, a considerable reduction up to 30-40% can make these technologies more competitive to other (waste)water treatment methods. Utilization of inexpensive raw materials (including recycled or naturally occurring materials) as well as the development of facile and cost-effective methods can be considered a potential approach to reduce the costs of MFC fabrication [189]. For instance, Feng et al [190] concluded that among the high-performance materials, SS electrodes (SUS 304) are the cheapest option (21 k$/m 3 ), followed by titanium plate and graphite felt (30 k$/m 3 , and 25-75 k$/m 3 , respectively).…”
Section: Sustainability Aspects and Future Outlookmentioning
confidence: 99%
“…The development of nanomaterials has often provided a breakthrough to overcome technological issues in diverse engineering fields because nanomaterials have various distinctive and outstanding properties that are not present in macro-or bulk-sized counterparts. Owing to their preferred properties, such as high electrical conductivity, high specific surface area, high durability, high cost-effectiveness, good catalytic capability for hydrogen evolution, and anti-microbial activity, various nanomaterials have been developed and applied to mitigate some of the aforementioned challenges of MECs by improving the characteristics and performance of critical components (i.e., anode/cathode electrodes, catalysts, and separators) or substituting high-cost components, as shown in Figure 3 [12,25]. To synthesize nanomaterials applied for MECs, various approaches for nanomaterials, such as thermal annealing, electrochemical anodization, and electrodeposition, have been reported, as summarized in Table 1.…”
Section: Nanomaterials Used In Microbial Electrolysis Cellsmentioning
confidence: 99%
“…The pan and sample are heated, and the weight is measured with the heating rate cycle. The weight loss was recorded and analyzed [26,35]. Thermogravimetric analysis is used to know the thermal stability of materials by withstanding temperature as it continues to increase with time as mass is recorded and by this mass loss to find the moisture content, volatile, ash, and moisture contents of the given sample…”
Section: Proximate Analysis Of Khat Wastementioning
confidence: 99%